2009
DOI: 10.1016/j.neuroscience.2009.04.024
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and intracellular relationships between the α7 nicotinic acetylcholine receptor and the vesicular acetylcholine transporter in the prefrontal cortex of rat and mouse

Abstract: The alpha-7 subunit of the nicotinic acetylcholine receptor (α7nAChR) is expressed in the prefrontal cortex (PFC), a brain region where these receptors are implicated in cognitive function and in the pathophysiology of schizophrenia. Activation of this receptor is dependent on release of acetylcholine (ACh) from axon terminals that contain the vesicular acetylcholine transporter (VAChT). Since rat and mouse models are widely used for studies of specific abnormalities in schizophrenia, we sought to determine th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
40
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 73 publications
(89 reference statements)
5
40
0
Order By: Relevance
“…The specificity of these antisera was described previously (Pickel et al, 2006; Duffy et al, 2009, 2011) and that of the D 2 R further confirmed in the dorsal striatum of MSN-D2R KO. Each receptor had a similar subcellular location when detected with either the immunogold or immunoperoxidase method, and reversal of markers assured that each antigen was optimally identified by methods having different sensitivities and resolution.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…The specificity of these antisera was described previously (Pickel et al, 2006; Duffy et al, 2009, 2011) and that of the D 2 R further confirmed in the dorsal striatum of MSN-D2R KO. Each receptor had a similar subcellular location when detected with either the immunogold or immunoperoxidase method, and reversal of markers assured that each antigen was optimally identified by methods having different sensitivities and resolution.…”
Section: Discussionsupporting
confidence: 76%
“…However, in dendrites smaller than 0.5-μm diameter and in small unmyelinated axons a single particle was considered positive immunogold-labeling, since almost no gold–silver deposits were seen over myelin and other tissue elements not known to express the receptors under examination. The validity of this approach was established previously for other receptors (Garzón et al, 1999; Garzón and Pickel, 2006) and has also been used for α7nAChR and D 2 R in the cerebral cortex (Duffy et al, 2009, 2011). In addition, however, we examined the number of gold particles over dendritic and axonal profiles in control experiments in which the tissue was processed for dual immunolabeling with the omission of one of the respective primary antisera to assess the level of background spurious gold–silver particles.…”
Section: Methodsmentioning
confidence: 71%
See 1 more Smart Citation
“…A host of other ligand-gated receptors and channels have been identified by pre-embedding methods, mainly concentrated along the spine plasma membrane, away from the PSD (but as noted above, these methods may fail to detect protein within the PSD), including dopamine and 5-HT receptors, nicotinic acetylcholine receptors, and EphA receptors (Miner et al 2000(Miner et al , 2003Riad et al 2000;Fabian-Fine et al 2001;Tremblay et al 2007;Duffy et al 2009). New data come from the "SDS-FRL" approach (sodium dodecyl sulfate-freeze-fracture replica labeling), in which freeze-fractured tissue is coated with an inert film of platinum and carbon (to protect proteins embedded in the membrane from subsequent digestion in hot SDS, which removes tissue from the back of the platinum-carbon replica) before immunolabeling (Fig.…”
Section: Molecular Anatomy Beyond the Psdmentioning
confidence: 99%
“…Thus, cholinergic cells can promote cortical activation, which underlies arousal, sensory processing and attention. The effect of ACh released through BF cholinergic axons in the cortex is complex due to: (1) the differential regional and laminar distribution of cholinergic axons; (2) different effects on various neuronal types and cellular sites of action (cell bodies, dendrites, axons); (3) ACh effects are mediated by synaptic and volume transmission at different time scales; and (4) ACh acts through a variety of muscarinic and nicotinic receptors (Levey et al, 1991;Mrzljak et al, 1996;Palomero-Gallagher and Zilles, 2004;Disney et al, 2007;Duffy et al, 2009;Parikh et al, 2010;Howe et al, 2010;Bell et al, 2011;Bennett et al, 2012) that are expressed differentially in pyramidal cells and in the various interneurons (Yamasaki et al, 2010). It seems that the complex effects of ACh fall in line with each specific neuronal cell type's role in the information processing architecture of the cortex.…”
Section: Introductionmentioning
confidence: 99%